MANAJEMEN HAK AKSES KONEKSI INTERNET MENGGUNAKAN SQUID PROXY SERVER DI RELOAD.NET - Ragil Prihantoro, Candra (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Internet as information resources have a role that is so important to the community . Things to consider is the Internet in interacting factors of the use of the Internet is the use of  Proxy Server is one of the solutions offered to provide Internet safety . One Proxy Server is quite popular today is Squid , Squid Proxy Server is the most widely used program by the network administrator as a program for squid proxy server is open source so it can be modified according to our wishes . Therefore we use the Squid to help in setting permissions in Internet networks required to provide information security data accessed by way of the filter so that the website - a website that can be accessed should not be blocked , limiting Internet bandwidth required in the network in an attempt to equally distribute owned bandwidth according to the number of clients in the Internet network.  Internet access required and Restrictions For Internet access can be used that are not held by the client who does not have the right to access the internet.                The method used for the design of an internet connection access rights management using a squid proxy server in reload.net consists of several stages: planning , data collection , analysis , design , system design , and preparation of reports.    The results of this research is the implementation of ACL Squid Proxy Server is configured by the server to limit the use of the internet so that the client can provide internet accessible data security.    Key words : Squid Proxy Server , Unblock sites , limiting bandwidth , restricting internet access